Religion and charity : the social life of goodness in Chinese societies - Weller, Robert P. (Robert Paul), 1953- (Cambridge University Press, 2018)
This book challenges our assumptions about morality by explaining how industrialized philanthropy and universalized goodness came to dominate Chinese religious engagement.